Kuliah Kerja Nyata Sebagai Implementasi Pendidikan Berbasis Masyarakat di Perguruan Tinggi - Apreriri Cahyani; Tuti Nurhaningsih; Netti Karnati; Desi Rahmawati (Institut Nalanda, 2024)
One form of implementing community-based education in higher education is through Practical Field Work (KKN), an educational activity that places students in the community to experience community life. The community is used as a partner of higher education as a direct learning resource; students can understand and identify the problems they face and provide immediate solutions. This research aims to provide an overview of the implementation of Practical Field Work at case study universities at the Faculty of Communication Sciences, Universitas Pancasila.